Sensory evaluation of pistachio spread using quantitative descriptive descriptive test. - Shakerardekani, Ahmad; Karim, Roselina; Mohd Ghazali, Hasanah; Chin , Nyuk Ling (2012)
Pistachio nut (pisfacia Vera L.) is one of the popular and nutritious tree nuts in the world. Pistachio spread is a new product which is made from pistachio paste, sugar, and palm oil. This paper involved development of suitable terminology for describing pistachio spread using quantitative descriptive analysis (QDA). The method is used to measure the quality of the two pistachio spreads formulated throughout the research (Formulation 1 including 50% paste, 30% sugar and 20% palm oil and Formulation 2 including 58.3% paste, 25% sugar and 16.7% palm oil). Eight panelists were selected for training and evaluation of pistachio spread. Twenty attributes (in terms of appearance, aroma, flavor, texture and aftertaste) were identified and developed for the product. No significant difference was observed in all attributes between the pistachio spread formulations except for sweetness (pc 0.05).